MOLECULAR IDENTIFICATION OF THE MOST PREVALENT MUTATION OF GLUCOSE-6-PHOSPHATE DEHYDROGENASE (G6PD) GENE IN DEFICIENT PATIENTS IN GILAN PROVINCE - M.R. Noori-Daloii (Journal of Sciences, Islamic Republic of Iran)
Glucose-6-Phosphate Dehydrogenase (G6PD) is a cytosolic enzyme which its main function is to produce NADPH in the red blood cells by controlling the step from Glucose-6-Phosphate to 6-Phospho gluconate in the pentose phosphate pathway. G6PD deficiency is the most common X-chromosome linked hereditary enzymopathy in the world, that result in reduced enzyme activity and more than 125 different mutations causing it have been identified. In the present study we analyzed peripheral blood samples of 103 unrelated patients with G6PD deficiency in GilanProvince in the north of Iran. DNA samples from these subjects were analyzed for the presence of certain known G6PD mutations by the appropriate restriction enzyme digestion of fragments, amplified by PCR. In this way, it revealed that Mediterranean mutation (C563T, Ser 188 Phe) is predominant in this area and 89 samples out of 103 (86.4%) have this mutation, indicating a higher prevalence of this mutation, in Gilan in Comparison to Mazandaran (66.2%). Among other patients, 10 samples (9.71%) have Chatham mutation (G1003A, Ala 335 Thr), but none of the samples was found to have Cosenza mutation (G1367, Arg 459 Pro).